Lipemic aqueous humor and suspected xanthomas associated with primary hypertriglyceridemia in a cat. Issue 3 (21st June 2021) - Barachetti, Laura; Fanton, Natalia; Savov, Stefan; Cancelli, Irene; Miller, Paul E.
Abstract: A 1‐year‐old, male neutered, European Shorthair cat presented for bilateral lipemic aqueous humour and mildly increased intraocular pressure in the left eye. Laboratory evaluations showed hypertriglyceridemia and elevation of alpha‐1‐globulins and serum amyloid‐A. The initial treatment plan consisted of topical flurbiprofen, tobramycin‐dexamethasone, dorzolamide and low‐fat diet. Lipemic aqueous resolved within 72 hours without recurrence. Presumed lipemic droplets were observed in the vitreous. Two months after the initial diagnosis the cat returned with dermatological changes, consisting of pale pink papules and erosions on the neck and ear pinna with pruritus. Cytology of these lesions was consistent with cutaneous xanthoma. A primary familial hypertriglyceridemia was confirmed by exclusion on the basis of normal abdominal ultrasound, urine test and repeated blood work after the change of the diet. The xanthomas resolved two weeks after further restriction of the diet. At 74‐weeks after initial presentation posterior subcapsular lenticular opacities appeared in both eyes.